Communication and exchange rate policy - Marcel Fratzscher (European Central Bank (ECB), 2004)
This paper deals with the very short-term influence of "oral interventions" on the exchange rate of major currencies. The paper finds that official communication, as reported by wire services, are effective in influencing the US dollar-euro and yen-US dollar exchange rates in the desired direction on intervention days. Oral interventions are found to be substantially more effective if they deviate from the prevalent policy "mantra". They also tend to reduce market volatility whereas actual interventions raise volatility. A key result of the paper is that oral interventions are effective independently from the stance and direction of monetary policy as well as the occurrence of actual interventions. This suggests that oral interventions might constitute, on a short-term basis, an effective and largely autonomous policy tool.
Keywords: E61; E58; F31; 330; communication; euro area; exchange rate; intervention; policy; United States